Community Policing in Madison, Wisconsin: Evaluation of Implementation and Impact, 1987-1990 - Wycoff, Mary Ann ([Verlag nicht ermittelbar], 1996)
This study sought to evaluate the Madison, Wisconsin, Police Department's creation of a new organizational design (both structural and managerial) that was intended to support community-oriented and problem-oriented policing. One-sixth of the organization serving approximately one-sixth of the community was used as a test site for the new community policing approach. This Experimental Police District (EPD) was charged with implementing "quality policing," which emphasized quality of service delivery, quality of life in the community, and quality of life in the workplace. For the first part of the program evaluation, attitude changes among officers working in the EPD were compared with those of officers working in the rest of the police department. Part 1, Commissioned Personnel Data, Wave 1, contains responses from 269 commissioned personnel surveyed in December 1987, before the creation of the EPD. Part 2, Commissioned Personnel Data, Wave 2, consists of responses from 264 police officers who completed a Wave 2 survey in December 1988, and Part 3, Commissioned Personnel Data, Wave 3, supplies responses from 230 police officers who completed a Wave 3 survey in December 1989. Although the analysis was to be based on a panel design, efforts were made to survey all commissioned personnel during each survey administration period. Police personnel provided their assessments on how successfully quality leadership had been implemented, the extent to which they worked closely with and received feedback from other officers, the amount of their interaction with detectives, the amount of time available for problem-solving, ease of arranging schedules, safety of working conditions, satisfaction with working conditions, type of work they performed, their supervisor, commitment to the department, attitudes related to community policing and problem-solving, perception of their relationship with the community, views of human nature, attitudes toward change, attitudes toward decentralization, and demographic information. As the second part of the program evaluation, attitude changes among residents served by the EPD were compared with those of residents in the rest of the city. These data are presented in Part 4, Residents Data, Waves 1 and 2. Data for Wave 1 consist of personal interviews with a random sample of 1,166 Madison residents in February and March 1988, prior to the opening of the EPD station. During the second wave, Wave 1 respondents were interviewed by telephone in February and March 1990. Residents provided their perceptions of police presence, frequency and quality of police-citizen contacts, estimates of the magnitude of various problems in their neighborhoods, evaluation of the problem-solving efforts of the police, perception of neighborhood conditions, levels of fear of crime, personal experience of victimization, knowledge of victimization of other residents, and demographic information.